Sports medicine conditions : return to play : recognition, treatment, planning - Miller, Mark D.; Chhabra, Anikar; Konin, Jeff G.; Mistry, Dilaawar J.; Griffin, Justin W. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2014)
"Sports Medicine Conditions: Return to Play addresses the most important and challenging problems in sports medicine, determining the appropriate time for an athlete to return to play. With this handy resource, you'll explore the latest imaging diagnostics, and get vital information on surgical and non-surgical therapies for athletic injuries. Look inside and discover ... Injury-based organization lets you find the facts you need quickly - Two-page spread format for each injury lets you find practical solutions at a glance - Consistent presentation covers History/Mechanism of Injury, Physical Examination, Imaging, Classification, Operative and Nonoperative Treatments, Rehabilitation Principles, and Return to Play - Expert perspectives let you benefit from the experience of orthopedics, sports medicine, and physical therapy professionals - Abundant original composite illustrations that clearly demonstrate operative procedures for these injuries"--Provided by publisher.